(untitled) (Journal of EAHIL, 2017)
Who do you think “Librarians of the Future” are? How would they behave and what would they look like? In my imagination they are like a space hero, a Flash Gordon-like figure with almost magical cyber librarian skills nobody ever has heard of. But hold on – many of us practice such skills already. Every time I listen to some of my colleagues from abroad I’m deeply astonished about the diversity of tasks they perform, the services they have invented, and the kind of non genuine library task they manage. (Maybe that’s the reason why every year I’m more content to be a librarian, and I cannot imagine a more powerful and amazing work.) Let me demonstrate some of the tasks and skills that I have come across: